A Comparative Typological Analysis of Passive Constructions in English and Uzbek: Structure, Function, And Discourse Patterns (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article presents a comparative typological analysis of passive constructions in English and Uzbek, examining how their structural, functional, and discourse-related features reflect broader distinctions between an analytic and an agglutinative language. Unlike earlier studies that focus mainly on formal similarities, this research adopts a functional–pragmatic approach, exploring how passives influence information flow, agent defocusing, and communicative intent. English relies primarily on auxiliary-based periphrastic passives, whereas Uzbek employs morphologically marked verb forms in which agent suppression is the default. The study also demonstrates how discourse norms, genre conventions, and cultural communication styles contribute to distinct passive preferences in each language.